Regio- and stereoselective synthesis of new diaminocyclopentanols - Larin, Evgeni A.; Kochubei, Valeri S.; Atroshchenko, Yuri M. (Beilstein Journal of Organic Chemistry, 2014)
The optimal conditions for regio- and stereoselective epoxide ring opening of N,N-disubstituted 1,2-epoxy-3-aminocyclopentanes by different nucleophilic reagents have been developed. The substituents on the nitrogen atom in the epoxide precursor and the orientation of the oxirane ring are crucial for the reaction outcome. Thus, treatment of (1RS,2SR,3SR)-1,2-epoxy-3-(N,N-dibenzylamino)cyclopentane (3b) with amines gave a mixture of C1 and C2 regioadducts, while the use of (1RS,2SR,3SR)-1,2-epoxy-3-(N-benzyl-N-methylamino)cyclopentane (3a) led ultimately to C1 adducts. Base-catalyzed aminolysis of epoxides 6a,b afforded mainly C1 adducts 13a,b arising from trans-diaxal opening of the epoxide ring. Using a Lewis acid catalyst, epoxides 6a,b were transformed into diaminocyclopentanols 14a,b via an alternative pathway involving the formation of aziridinium intermediate 17.
Keywords: diaminocyclopentanols; epoxides; regioselectivity; ring opening; stereoselectivity